PEMANFAATAN TUMBUHAN BAWAH SEBAGAI OBAT OLEH MASYARAKAT SEKITAR HUTAN TAMAN HUTAN RAYA SULTAN THAHA SYAIFUDDIN PROVINSI JAMBI - Albayudi, Albayudi; Saleh, Zuhratus (Wahana Forestra: Jurnal Kehutanan, 2020)
In some conservation forest areas, interaction between local communities and natural resources is still very strong. The people who live around Taman Hutan Raya Sultan Thaha Syaifuddin Jambi Province are known to still use some species of plants for medicinal purposes. The tradition and knowledge of local people in the rural areas about the use of plants to meet their daily needs has been going on for a long time even before an area is designated as conservation forest. The purpose of this study was to inventory the species of plants that are used as medicine by the community around Tahura STS Jambi, especially the understorey. This research was conducted at Tahura STS Jambi in July-September 2018. The method used in this study were interviews and surveys directly in the field so we only documented every kind mentioned by the informants and has a presence in the field. The results of the study showed that 22 lower-level plants were used as medicine by the community around Tahura. These plants are used as medicine for various medical and non-medical diseases. This number of species is considered as an indicator of decreased knowledge and utilization of medicinal plants by communities around forest.